2020
DOI: 10.1038/s41598-020-59364-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial DNA promotes Tau aggregation

Abstract: A hallmark feature of Alzheimer's disease (AD) and other tauopathies is the misfolding, aggregation and cerebral accumulation of tau deposits. Compelling evidence indicates that misfolded tau aggregates are neurotoxic, producing synaptic loss and neuronal damage. Misfolded tau aggregates are able to spread the pathology from cell-to-cell by a prion like seeding mechanism. The factors implicated in the initiation and progression of tau misfolding and aggregation are largely unclear. In this study, we evaluated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 67 publications
(94 reference statements)
3
45
0
Order By: Relevance
“…Recently we have conducted an analysis and identified for the first time viral prion-like domains (PrDs), which we suggest are novel regulators of virion assembly with a role in virus-host cell interactions (12,13). These studies were in alignment with previous studies, showing that in addition to the pathological role of prions that they play in humans being implicated in Alzheimer's and Parkinson's diseases, diabetes, and many other human pathologies, protein misfolding plays important physiological roles in eukaryotes and prokaryotes (14)(15)(16)(17).…”
Section: Introductionsupporting
confidence: 79%
“…Recently we have conducted an analysis and identified for the first time viral prion-like domains (PrDs), which we suggest are novel regulators of virion assembly with a role in virus-host cell interactions (12,13). These studies were in alignment with previous studies, showing that in addition to the pathological role of prions that they play in humans being implicated in Alzheimer's and Parkinson's diseases, diabetes, and many other human pathologies, protein misfolding plays important physiological roles in eukaryotes and prokaryotes (14)(15)(16)(17).…”
Section: Introductionsupporting
confidence: 79%
“…Pathological tau has also been shown to determine translational selectivity and co-localize with ribosomes (Koren et al, 2019;Meier et al, 2016) . P. gingivalis DNA promotes aggregation of tau (Tetz et al, 2020) , and it has been postulated that tau fibrillization may block cytoskeleton-trafficking infections agents (Moir et al, 2018) . While speculative, the ER translocation genes point to mechanisms that link the gingipain hypothesis of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically modified mice in which Aβ plaque formation is enhanced or tau phosphorylation is accelerated have been a valuable tool to determine host-microbe interactions in the context of AD. In vitro studies have also demonstrated that bacterial components such as lipopolysaccharide (LPS), a highly immunogenic cell wall component of Gram negative bacteria, and bacterial DNA can lead to enhanced Aβ accumulation and tau misfolding (Table 1 ) [ 23 , 88 ]. This was further demonstrated in vivo by Sheng et al via intraperitoneal administration to of E. coli -derived LPS to APPswe mice, which lead to enhanced neuroinflammation and neuronal Aβ accumulation (Table 1 ) [ 24 ].…”
Section: A Nontraditional View Of Admentioning
confidence: 99%